The Historicity of the Earthquakes Occurring in the Iberian Peninsula before A.D. 881 Recorded in Spanish and Portuguese Seismic Catalogs - Álvarez-Martí-Aguilar, Manuel (Seismological Society of America, 2020)
In this paper, the original accounts of the first 19 earthquakes—occurring before 881 AD—recorded in Martínez-Solares and Mezcua’s Catálogo sísmico de la Península Ibérica (2002) are reviewed. Their evolution is traced through references to them in the works of Spanish and Portuguese historians and authors published between the 16th and 19th centuries, and it is shown how they subsequently made their way into the main Spanish and Portuguese seismic compilations and catalogues. By identifying the first references to news of historical earthquakes in the Iberian Peninsula in the literary sources, the intention is to gain a better understanding of the context in which this information originated over time and to verify its historicity with greater precision. The review performed here shows that the majority of these accounts lack a firm historical basis.
Keywords: Terremotos - Historia - Península Ibérica; Earthquakes; Tsunamis; Iberian Peninsula; Historical Seismology